Model of regional policy involving the population in systematical physical education and sports - Abalyan A.G. ,; Fomichenko T.G. ,; Bogomolov G.V. ,; Zyurin E.A. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop a model of regional policy aimed at increasing the effectiveness of involving the population in systematic physical education and sports. Methods and structure of the study. The work carried out: analysis of management functions, statistical data in form No. 1-FK, No. 3-AFK, No. 2-GTO, modeling, pedagogical design. Results and conclusions. Based on the analysis and systematization of official data from Rosstat statistical indicators for the period 2018-2022. The article presents a model of regional policy aimed at increasing the effectiveness of involving the population in systematic physical education and sports. The developed model is the basis for the formation of programs, technologies and mechanisms for involving (motivating) the population in systematic physical education and sports in the regional space.